Investigation on the impact of speed humps towards travel delays in rural roads - Farida Hamimi, Ismasafie (2019)
Traffic calming device is widely used, not just in Malaysia to increase the safety of the road users including the motorcyclist, bicyclist and pedestrian but also in many countries around the world. Among the calming devices used are speed humps, speed bumps, speed tables, roundabouts, transverse rumble strips, optical speed bars, textured pavement and cat-eye reflectors. This traffic calming is designs or modifies to ensure the uniform speeds of vehicles are controlled. It tends to force the vehicle to slow down. Speed hump is a raised section of asphalt vertically crossing a road. They are usually parabolic, semi-circular or sinusoidal in shape. This speed hump installation usually increase travel times as drivers have to undergo a process of decelerations and accelerations while crossing the hump. Speed humps are usually made from rubber, concrete, plastic or asphalt. Based on Arahan Teknik Jalan JKR (18/97) the height for hump for type 1 is between 100 mm to 150 mm and type 2 is between 80 mm to 150 mm with a length of 3000mm for type 1 and 6000mm to 10000mm for type 2. 3 sinusoidal speed humps were used in this study. Speed hump 1 is measured as having 91mm height and 2800mm width. Meanwhile, speed hump 2 is having a height of 52mm with 3070mm width and 59mm height and 3020mm widths for speed hump 3. The height and length of the speed hump is determined by meter ruler and walking meter and the delay caused by the speed humps is observed by a 60m road without humps travel time and a 60m with humps travel time by stopwatch. The differences in terms of height and width of these speed humps have resulting different time taken and delay across the whole 60m road where these humps is located. Total travel time taken for this 60 m road without the presence of humps was calculated as 3.11sec at the speed of 37km/h. However, with a presence of these humps the total travel time was increased to 5.32sec at the same speed. The average time taken to cross speed hump 1 is 6.99 sec, 5.53 sec for speed hump 2 and 6.51 sec for speed hump 3. As a conclusion, the height and length of a speed humps do resulting different time delay as speed hump 1 is 91mm height and 2800mm width with longest time travel which is 14.35sec, speed hump 2 is 52mm and 3070mm width with longest time travel 11.59sec and speed hump 3 with height 59mm and 3020mm width with longest time travel 11.81sec.